The brothers of Baker Street [large type] - Robertson, Michael, 1951- (Thorndike Press large print mystery, 2011)
The first Sherlock Holmes letter barrister Reggie Heath answered cost him most of his personal fortune, all of his Baker Street Chambers clients, and quite possibly the love of his life. But Reggie intends to earn all of it back again. His latest client is the driver of one of London's famous Black Cabs, accused of murdering two American tourists. But while Reggie is working on that case, the letters to Sherlock Holmes are piling up.